2010
DOI: 10.1523/jneurosci.4301-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Caudal Medial Entorhinal Cortex: a Selective Role in Recollection-Based Recognition Memory

Abstract: Recent studies have suggested that the caudal medial entorhinal cortex (cMEC) is specialized for path integration and spatial navigation. However, cMEC is part of a brain system that supports episodic memory for both spatial and nonspatial events, and so may play a role in memory function that goes beyond navigation. Here, we used receiver operating characteristic analysis to investigate the role of the cMEC in familiarity and recollection processes that underlie nonspatial recognition memory in rats. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 33 publications
7
29
0
Order By: Relevance
“…Overall, our work extends previous findings that have demonstrated temporal coding over a mnemonic delay in MEC grid cells (Kraus et al, 2015), as well as work that has implicated MEC activity in enabling memory over time (Sauvage et al, 2010, Suh et al, 2011, Kitamura et al, 2014). Here we offer direct evidence for a medial entorhinal role in the coherent orchestration of hippocampal temporal firing patterns important for memory.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our work extends previous findings that have demonstrated temporal coding over a mnemonic delay in MEC grid cells (Kraus et al, 2015), as well as work that has implicated MEC activity in enabling memory over time (Sauvage et al, 2010, Suh et al, 2011, Kitamura et al, 2014). Here we offer direct evidence for a medial entorhinal role in the coherent orchestration of hippocampal temporal firing patterns important for memory.…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has shown that MEC activity is also crucial for successful memory across a delay (Sauvage et al, 2010, Suh et al, 2011, Kitamura et al, 2014), and reported temporal firing fields in MEC grid cells (Kraus et al, 2015). MEC lesions disrupt the precise spike timing of CA1 neurons relative to the phase of the theta rhythm (Schlesiger et al, 2015), suggesting that MEC may also support the temporal organization of hippocampal time cell sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the MEC is not required to successfully recognize a context, detect a spatial change, associate a tone and shock, or recognize an object. Other work suggests that this area is critical for performance on non-spatial tasks that require the flexible use of memory (Sauvage et al, 2010; Navawongse and Eichenbaum, 2013). Thus, the MEC is not specialized for all forms of hippocampus-dependent memory, but does appear critical for a limited range of tasks, including normal acquisition and use of place memory.…”
Section: Discussionmentioning
confidence: 99%
“…Following the ‘where’ stream further towards the hippocampus, lesions of the medial entorhinal cortex — an area commonly associated with spatial representation — impair memory of the temporal context of recently experienced stimuli 60 , and entorhinal inputs to the hippocampus are essential for bridging temporal gaps between associated events 61,62 . Furthermore, there is recent evidence that medial entorhinal cortex neurons that fire when a rat is in particular locations in space (known as ‘grid cells’) also fire at particular moments during treadmill running 63 .…”
Section: Origins Of Timing In the Hippocampusmentioning
confidence: 99%